(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
Speech goes in the article about nominative presentations mean of expressive syntax. Paid attention to stylistic functions of the mentioned constructions. An idea is reasonable, that nominative presentation is special of nominative constructions, which is marked an artistically-graphic capacity, expressive colouring.